2020
DOI: 10.1016/j.eclinm.2020.100418
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab for treatment of patients with severe COVID–19: A retrospective cohort study

Abstract: Background: Tocilizumab was approved for chimeric antigen receptor TÀcell therapy induced cytokine release syndrome and it may provide clinical benefit for selected COVIDÀ19 patients. Methods: In this retrospective cohort study, we analyzed hypoxic COVIDÀ19 patients who were consecutively admitted between March 13, 2020 and April 19, 2020. Patients with lung infiltrates and elevated inflammatory markers received a single dose of tocilizumab if no contraindication was present. Systemic steroid, hydroxychloroqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
153
1
6

Year Published

2020
2020
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(172 citation statements)
references
References 27 publications
12
153
1
6
Order By: Relevance
“…The findings of leukocytosis associated with prolonged hospital admission in sickle cell patient with COVID-19 infection in this study was consistent with the observation of significant correlation between leukocytosis and the severity of COVID 19 infection in a study by Gleng et al in 2020 [31]. It can also be explained by the study of Suwa et al that demonstated that IL-6 induces both neutrophil demargination in the blood vessel and reduction in neutrophil transit time to exit the bone marrow [35].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of leukocytosis associated with prolonged hospital admission in sickle cell patient with COVID-19 infection in this study was consistent with the observation of significant correlation between leukocytosis and the severity of COVID 19 infection in a study by Gleng et al in 2020 [31]. It can also be explained by the study of Suwa et al that demonstated that IL-6 induces both neutrophil demargination in the blood vessel and reduction in neutrophil transit time to exit the bone marrow [35].…”
Section: Discussionsupporting
confidence: 92%
“…Also the observation of markedly elevated C-reactive proteins and IL-6 in was identical to the finding by Mehta et al who noticed SARS-COV 2 induces upregulation of pro-inflammatory cytokines such as (IL-1, IL-6 and TNF-α) [30], this finding was also comparable with the study by Zhang et al in 2020 that demonstrated increase in total number of mortality in patients with condition associated with exaggerated release of cytokine known as cytokine release syndrome [10]. This was also in agreement with the study by Kewan et al in 2020 that has shown the efficacy of Tocilizimab (an anti-human IL-6 receptor monoclonal antibody), which inhibits signal transduction through the IL-6 receptor by binding to sIL-6 receptor and mIL-6 receptor [31].…”
Section: Discussionsupporting
confidence: 83%
“…[26][27][28] Treatment with IL-6 antagonists improved the survival and shortened the recovery time. [29][30][31][32][33] However, the cell types responsible for increased IL-6 expression in the lung are poorly defined, and understanding the relationship among IL-6 expression, the extent of SARS-CoV-2 infection, and disease severity is incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…There are reports that patients with COVID-19 have elevated levels of acute-phase reactants and inflammatory cytokines leading to cytokine release syndrome (CRS), and tocilizumab is effectively used in in-hospital patients admitted with CRS [134]. Kewan et al (2020), in their retrospective cohort study, analyzed the resulted favorable outcomes in hypoxic COVID-19 patients who were consecutively admitted between March 13, 2020, and April 19, 2020, and treated with a single intravenous infusion of low-dose tocilizumab. By May, an increasing number of studies had reported the use of tocilizumab in treating COVID-19.…”
Section: Drug Therapy In Covid-19mentioning
confidence: 99%